Coordination of biradial-to-radial symmetry and tissue polarity by HD-ZIP II proteins - Monica Carabelli (Nature Portfolio, 2021)
The apical style in Arabidopsis is formed following a bilateral-to-radial symmetry transition in the gynoecium. Here the authors show that the final step in style radialization is coordinated by the adaxial regulators HAT3 and ATHB4, which are induced by the SPT and HEC transcription factors.